A percepção dos usuários de um centro de reabilitação vinculado ao SUS: enfoque fonoaudiológico baseado na promoção da saúde. - Cunha, Jenane Topanotti da (2015)
Introduction: Evaluations about the quality of the service of the public services, by its users, have been the current focus of research in the field of health. Social Participation, as an organizational principle of the Unified Health System (SUS), has been guiding such research, insofar as this principle emphasizes the protagonism of the subjects who use health services. Objective: To verify the perceptions SUS users have regarding a Service Center, as well as the speech and language services provided at this Center. Method: Cross-sectional field research, composed by interview conducted in August 2013, with 111 subjects that use SUS and residents in the municipality of Cascavel-PR. The quantitative analysis was performed using the GraphPad Prisma 5.1, SPSS 15.0 and D "agostino and Person tests, comparative non-parametric F and Chi-square tests. The qualitative approach was based on content analysis. Results: The evaluation of the Customer Service Center with its physical structure and secretarial staff was well qualified by SUS users. Likewise, speech-language pathology services were well evaluated for aspects related to the queue, the user's expectations regarding the speech-language work, the explanations provided by the speech-language pathologist regarding the activities developed. Conclusion: Knowledge of civil law relating to health is part of an indispensable process for the qualification of public services. The reflexes generated by the incentive of a model of society with greater social participation lie in the construction of a more just and egalitarian society as a proposal for Health Promotion.